Loxapine in patient with clozapine-resistant psychosis - Jennifer Erley, PharmD, MBA, BCPS; Sarah Goldsborough, PharmD; Amy VandenBerg, PharmD, BCPP; Alexandra Audu, MD (American Association of Psychiatric Pharmacists, 2021)
Clozapine is recognized as the drug of choice for treatment-refractory schizophrenia, but use may be limited because of strict monitoring requirements and adverse effects including severe neutropenia, seizures, and myocarditis. Loxapine is a first-generation antipsychotic with similarities to clozapine in both structure and receptor binding. This case describes a 57-year-old male with a history of severe paranoid schizophrenia despite treatment with clozapine and other psychotropic agents, who experienced clinical improvement after a cross titration from clozapine to loxapine. Loxapine may be a reasonable alternative in patients with treatment-refractory schizophrenia who do not tolerate or respond to clozapine.